Quality effects of sodium alginate coating cross-linked with CaCl2 on Mugil liza fillets during storage - Vargas-Ramella, Márcio; da Silva, Débora; Dilarri, Guilherme; Zortea, Antonella Valentina Lazzari; Mendes, Carolina Rosai [UNESP]; de Souza Laurentino, Gabriel; Campagnol, Paulo Cezar Bastianello; de Oliveira, Aline Fernandes; da Silveira, Cristian Berto (Elsevier, 2025)
The global food preservation strategy involves plastic packaging, but these materials resist to degradation, raising environmental concerns. A promising alternative to solve this problem is using biopolymers as edible coatings. Bearing this in mind, the present study aimed to evaluate the feasibility of a sodium alginate edible coating cross-linked with CaCl2 (AGC) on lebranche mullet (Mugil liza) fillets' quality. Fillets (∼130 g) were purchased from a local fisherman in Laguna, Santa Catarina, Brazil. Then, samples were transported on ice to the laboratory for analysis (day 1 of the experiment). Our study compared AGC treatment to fillets without edible coatings (vacuum-packed in plastic bags) and to those treated with sodium alginate alone (with and without vacuum-packed in plastic bags) over 12 days of refrigerated storage (4 °C). In addition, the edible films were characterized by their morphological properties (Scanning Electron Microscope – SEM and Moisture content). The AGC treatment improved the films with a more homogeneous surface (SEM micrographs) and decreased (p < 0.05) the moisture content of the films in 44%. Considering the fillets parameters, AGC coating promoted during experiment lower (p < 0.05) values of total volatile base nitrogen (TVB-N) (13.48 mg/100g; day 12), mesophilic bacteria (4.51 CFU/g; day 9), Enterococcus spp. (4.92 CFU/g; day 12), and Escherichia coli (4.02 CFU/g; day 12). Our findings suggest that cross-linked coats may enhance the efficacy of the coating in controlling microbial counts and TVB-N. Nevertheless, AGC treatment increased lipid oxidation (12.58 mg MDA eq/kg sample) in the fillets. Therefore, further studies are needed to clarify the mechanisms of lipid oxidation when using this formulation and explore ways, such as including natural antioxidants in the coatings, to reduce the thiobarbituric acid reactive substances (TBARS) during storage.
Keywords: Calcium chloride; Food safety; Mullet fish; Natural polymer; Shelf-life; Vacuum-packaging